Chromosome Instability in Pony of Esperia Breed Naturally Infected by Intestinal Strongylidae - Emanuele D’Anza; Francesco Buono; Sara Albarella; Elisa Castaldo; Mariagiulia Pugliano; Alessandra Iannuzzi; Ilaria Cascone; Edoardo Battista; Vincenzo Peretti; Francesca Ciotola (Animals, 2022)
The Pony of Esperia is an Italian autochthonous horse breed reared in the wild on the Aurunci and Ausoni Mountains. Currently, it is considered an endangered breed, as its population consists of 1623 animals. It is therefore essential to identify all aspects that can improve the management and economy of its breeding, favoring its diffusion. In this paper, the effects of intestinal strongyle infection on the chromosome stability of peripheral blood lymphocytes (PBLs) was evaluated through aneuploidy and chromosome aberration (gap, chromatid and chromosome breaks, and the number of abnormal cells) test. Statistical difference in the mean values of aneuploidy, cells with chromosome abnormalities, and chromosome and chromatid breaks were observed between ponies with high fecal egg counts (eggs per gram > 930) and those with undetectable intestinal strongylosis. The causes of this phenomenon and possible repercussions on the management of Pony of Esperia are discussed in the paper.